Investigation of alternative blasting process in terms of impact behaviour of blasting materials for green shipyards - Alankaya, Veysel; Celebi, Ugur Bugra (INDERSCIENCE ENTERPRISES LTD, 2015)
Blasting process in shipyards could be marked as one of the most significant sources of waste; thus, it is considered mandatory for the surface preparation before painting process in new shipbuilding or for the removal of the old paint from the surface of old vessels. The particulate emissions are contaminated by blasting abrasives and paint chips during surface preparation processes and might contain toxic metals concerning the production area, off-site and surrounding surface waters when blown off-site. Environmentally friendly shipyards have gained more importance due to global warming and its undeniable effects. Therefore, replacement of traditional production methods with less contaminating, more environmentally safe and alternative processes which do not affect human health as much is vital. In this study, abrasive-blasting materials for surface preparation are investigated by means of impact effectiveness of the material. The numerical results, derived from a commercial dynamic explicit finite element program, are presented denoting the blasting efficiency and damage behaviour by material type, material geometry and particle velocity. A new point of view regarding choosing blasting material, decreasing amount of waste and pollution for a green world is tried to be presented.
Keywords: pollution sources; shipbuilding and ship repair industry; blasting materials; waste minimisation; PAINT FILMS; PARTICLES; Environmental Sciences & Ecology